P254 Identifying MMP-12 Substrates as Therapeutic Targets in COPD. (19th November 2012) - Mallia-Milanes, B; Clements, D; Sheehan, A; Bolton, C; Johnson, SR
Abstract : Background: Matrix metalloprotease (MMP)-12 is a key protease in COPD which cleaves pulmonary extracellular matrix and non-matrix substrates. Variation in MMP-12 activity affects severity of COPD, yet the mechanism of this, including MMP-12's non-matrix substrates in COPD lungs are unknown. Targeting MMP-12 substrates may lead to the development of drugs for COPD with reduced side effects compared to the broader spectrum MMP inhibitors. Aims: To identify MMP-12 substrates of relevance to COPD and determine how their activity affects disease progression in vitro and in vivo . Methods: In vitro cleavage assays: After literature review the pro-inflammatory mediators osteopontin and tumour necrosis factor (TNF)-α were selected as potential MMP-12 substrates in COPD. Both were incubated with MMP-12 and reaction products analysed by silver stain and western blot. EDTA was used as a metalloprotease inhibitor and thrombin as positive control. COPD cohort: Patients with COPD were recruited during exacerbations at the Nottingham University Hospitals NHS Trust. Sputum, lung function and other data were collected on Day 0 and 1 and 4 weeks later. Sputum was analysed by western blot for proteins of interest. The study was approved by the local research ethics committee and all patients gave informed consent. Results: MMP-12 cleaved osteopontin and pro-TNF-α in a dose and time-dependent manner when visualised by silver staining. Cleavage was dependent on MMP-12 activity as it was inhibited by EDTA. Western blot of cleaved protein fragments gave a characteristic band signature. MMP-12 was present in sputum of patients with COPD as demonstrated by western blotting, ELISA and casein zymography. Western blot analysis of sputum with anti-osteopontin antibodies showed a similar band signature to the in vitro cleavage suggesting osteopontin is cleaved in the airways of patients with COPD. Discussion: MMP-12 possesses proteolytic activity against osteopontin and pro-TNF-α in vitro . MMP-12, osteopontin and TNFα are present in COPD sputum and our data suggest that MMP-12 may target osteopontin in COPD. Further work is needed to determine the precise mechanisms of such MMP-12 substrate activity in COPD.